Artificial intelligence in strategic business management: The case of auditing - Résio, Mariana Catarino (2020)
The strategic realignment of a company seeks to strengthen its potential and create value so that it stands out in the market and achieves better results. We live in the era of digital transformation and adopting innovative tools and technologies such as Artificial Intelligence seems to be extolling business models and driving optimization in the processes inherent to their operation. If we look specifically to the audit area, which is intense in tasks that can be performed by machines, studies emerge showing positive results in the adoption of AI tools. After collecting data from previous investigations on the topic, we found that the use of machinery such as Artificial Intelligence in business models opens doors to the creation of value in organizations adjacent to this strategy. However, the adoption of such tools seems to be scarce. In order to deepen this contradictory approach between the benefits associated with the adoption of AI and the low rate of use of it, around 200 employees from mostly Portuguese companies were inquired. The analysis of the results obtained allows us to conclude that the scenario projected by the employees is auspicious even though the respective companies seem to be reluctant to take this step. Thus, this investigation reveals that the reasons seem to be related to misinformation, fear that unemployment will increase and fear about the costs associated with this transformation and opens the door for future investigations on these points.